The value of a network - Wills-Johnson, Nick; Hornby, P. (Canadian Centre of Science and Education, 2007)
This paper presents a simple mechanism for quantifying the value which a network createsbased upon the way in which it is connected. The mechanism is grounded in a process of information sharing by nodes and is, in a sense, an extension of Bonacich’s (1972) centrality measure.